MENEMUKENALI BERBAGAI ALTERNATIF INTERVENSI DALAM MENGHADAPI QUARTER LIFE CRISIS: SEBUAH KAJIAN LITERATUR [DISCOVERING VARIOUS ALTERNATIVE INTERVENTION TOWARDS QUARTER LIFE CRISIS: A LITERATURE STUDY] - Muhammad Syifa'ussurur; Nurul Husna; M Mustaqim; Lukman Fahmi (Perkumpulan Ahli Bimbingan Konseling Islam (PABKI) Indonesia, 2021)
Early adulthood is a period of transition from adolescence to adulthood which becomes a complex transition. There are many stressors that lead to various difficulties, so that individuals feel trapped and lost their way in adulthood. This condition is known as the quarter life crisis, which is a common phenomenon that occurs at the age of 20-30 years. This phenomenon is influenced by various factors, both internal and external factors. The purpose of this paper is to examine various alternative interventions that can be carried out in order to deal with a quarter life crisis. The strategies that can be carried out as an intervention to prevent a quarter life crisis are to stop comparing yourself with others and get to know yourself better, turning doubts into actions, finding people who can become support systems, limiting the use of social media, learning to love yourself, and solution-focus therapy.